Exploring the temporal shift in menstrual hygiene practices among young women across India: a micro and macro perspectives - S. K. Singh; Bharti Singh (Frontiers in Reproductive Health)
BackgroundLack of menstrual hygiene practices (MHP) is one of the primary causes of reproductive morbidities among young women. The recent National Family Health Survey (NFHS) showed a significant increase in the use of hygienic menstrual methods in India. This paper aims to investigate the spatial and temporal changes in the prevalence of hygienic menstrual practices from 2016 to 2021, considering micro and macro perspectives.MethodThe study is based on women aged 15–24. The Datasets used in this study are from two recent rounds of the National Family Health Survey, NFHS-4 and NFHS-5. Descriptive, bivariate, multilevel, spatial, and Fairlie decomposition methods have been used to analyze spatial and temporal changes in MHP.ResultsThe study illustrates that the prevalence of MHP has increased by 20% points over the past five years, with a significant rise in the use of sanitary napkins, even among marginalized groups. Spatial variation and temporal changes reveal the influence of geospatial attributes, awareness, education, sanitation, and economic prosperity on MHP. Multilevel analysis portrays the maximum clustering in the MHP at the household level in both survey years. Further, Fairlie decomposition reveals that media exposure, followed by the educational attainment of women, contributes highest to the increase in MHP from NFHS-4 to NFHS-5.ConclusionThe findings of the study present a significant amount of influence of geospatial attributes, including culture and tradition. The extent of “awareness” regarding menstrual hygiene emerged as the most critical driver of escalating MHP in the country. Therefore, addressing socio-economic disparities and implementing interventions through community-level programs, preferably by adopting peer-based approaches with the active participation of self-help groups and frontline workers, is necessary to ensure universal access to sanitary methods.